2015
DOI: 10.5812/ijp.2005
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Oral Ibuprofen in Treatment of Patent Ductus Arteriosus in Full-Term Neonates

Abstract: Background:Patent ductus arteriosus (PDA) is an important risk for heart failure due to left to right shunt in term neonates.Objectives:In this study, we evaluated the effect of high dose ibuprofen in closure of PDA in term neonates.Patients and Methods:We used double dose ibuprofen (20 mg/kg, 10 mg/kg, and 10 mg/kg) for 3 - 30 day old term neonates with PDA who were admitted in the neonatal wards of Shiraz University of Medical Sciences. The results of this study were compared to the data of the previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, there was no difference between surgical and interventional methods in most studies according to the outcome (14)(15)(16)(17). Some studies have shown that ASD closure reduces the size of the right anatomical structures and increases the left side of the heart (18). Blood flow and TDI data of patients were also examined and compared to normal cases by researchers.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no difference between surgical and interventional methods in most studies according to the outcome (14)(15)(16)(17). Some studies have shown that ASD closure reduces the size of the right anatomical structures and increases the left side of the heart (18). Blood flow and TDI data of patients were also examined and compared to normal cases by researchers.…”
Section: Discussionmentioning
confidence: 99%
“…If the sample size is increased, and the infants are separated based on their gestational age and birth weight, significant differences may be observed. Third, this is a new treatment strategy with a great controversy as some studies found that the use of high doses of ibuprofen [ 9 , 20 , 21 ] or use of higher doses of ibuprofen with increasing age [ 9 ] can significantly increase the closure rate but not the adverse events. In our study, the time when ibuprofen was administered in the conventional treatment group was relatively later, and the dosage used was consistent with that in the prophylactic treatment group, which was a dose that is currently recognized as a lower dose; this may affect the therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin synthetase has two different activities including cyclooxygenase and peroxidase. Acetaminophen inhibits prostaglandin synthesis at the peroxides’ segment ( 7 ) while Ibuprofen is cyclooxygenase inhibitor ( 10 ).…”
Section: Discussionmentioning
confidence: 99%